INVESTIGATION OF SECONDARY TRANSFORMATIONS WITHIN LOWER CARBONIFEROUS ROCKS OF THE CENTRAL PART OF THE DNIEPER-DONETS DEPRESSION - Tunik О. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The article describes the main study results of the secondary transformations effect on the lower Carboniferous shales at depths exceeding 3 000 m. Using silicate, energy-dispersive X-ray fluorescence analysis and electron microscopic studies, the structure and the main rock-forming components in core samples were studied. The study showed the presence of both background and imposed epigenetic changes in the studied core samples. The intensity and variety of the secondary transformations increase with depth. It has been confirmed that compaction of clay rocks reduces their porosity and improves sealing properties. The presence of scattered siltstone material does not affect the value of porosity. Porosity increases with increasing of kaolinite content which occurred in result of secondary imposed processes. According to the composition of mineral paragenesis, it was found that the studied shales are at the stage of mesocatagenesis. The further research development for the purpose of approximation of microscopic and geochemical data by means of the extended well logging suit was outlined.